Hybrid CNN Transformer Architecture For Enhanced Eeg Based Emotion Recognition: Capturing Local And Global Dependencies With Self Attention Mechanisms - Kasthuri Devarajan; Suresh Ponnan; Sundresan Perumal (Springer Nature, 2026)
Indexed by WOS/ Scopus